Digitalized Drones in the Steel Industry: The Social Shaping of Technology - Stroud, Dean; Timperley, Victoria; Weinel, Martin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
New digital technologies are often framed as an inevitable and determining force that presents the risk of technological unemployment and the end of work (Lloyd and Payne, 2019). In manufacturing specifically, digitalization is referred to as Industry 4.0, a term that emerged in Germany as a central economic and industrial policy and has taken on a wider resonance across Europe (Pfeiffer, 2017). In this article, we explore the workplace implications of a specific Industry 4.0 innovation. We examine the insertion of drone technology—as a timely and topical example of industrial digital technological innovation—in the steel industry.The article brings to debates on the digital workplace a discussion of the relationship between the material forces of production and the social relations within which they are embedded (Edwards and Ramirez, 2016). Drawing on interview data from two European industrial sites, we suggest that the increasing use of drones is likely to be complicated by a number of social, economic and legal factors, the effects of which are, at best, extremely difficult to predict. Introduced for their potential as labour-saving devices, drones seemingly offer a safer and more efficient way of checking for defects in remote or inaccessible areas.However, whilst employers might imagine that digital technologies, like drones, might substitute, replace, or intensify labour, the workplace realities described by our interviewees make insertion highly contingent. We highlight several such contingencies, with examples of the ways that the steelworkers’ interests differ from those of their employers, to discuss how the insertion of digital technologies will ultimately be shaped by the power, interests, values and visions prevailing in the workplace, as well as in the wider polity and public culture.